Respuesta :
Answer:
x= -6 x=2
Step-by-step explanation:
x^2 + 4x - 12 = 0
Factor, what 2 terms multiply to -12 and add to 4
6* -2 = -12
6+-2 = 4
( x+6) (x-2) =0
Using the zero product property
x+6 =0 x-2=0
x= -6 x=2
Answer:
option C will be the correct answer
x= 2 or x = -6
Step-by-step explanation:
[tex]x {}^{2} + 4x - 12 = 0? \\ {x}^{2} + 6x - 2x - 12 = 0 \\ x(x + 6) - 2(x + 6) = 0 \\ (x - 2)(x + 6) = 0 \\ x - 2 = 0 \: \: \: \: or \: \: \: \: x + 6 = 0 \\ x = 2 \: \: \: \: or \: \: \: \: x = - 6[/tex]